The effectiveness of the police's role in dealing with thuggery in Serang Regency - Dimas Putro Nugroho; Sulkiah Hendrawati; Wahyudi Wahyudi (Journal of Law Science, 2024)
This study aims to analyze the effectiveness of the police's role in combating thuggery in Serang Regency. Thuggery, as a form of social crime, not only disrupts public order but also causes public unrest and hinders regional development. The research method used is a qualitative approach with data collection techniques through interviews, observations, and documentation studies. Research informants consisted of police officers, community leaders, and parties involved in efforts to combat thuggery. The results of the study indicate that the police have implemented several strategies, including repressive actions in the form of raids and law enforcement, preventive actions through routine patrols and legal socialization, and pre-emptive actions by establishing cooperation with the community to increase legal awareness. However, the effectiveness of these efforts still faces obstacles, such as limited police resources, a permissive culture of some communities towards thuggery practices, and weak coordination with other agencies. The conclusion of this study is that the police's role is quite effective in reducing the number of thuggery acts, but to achieve optimal results, stronger synergy is needed between the police, local government, and the community. This study recommends increasing the capacity of officers, optimizing community development programs, and strengthening regional regulations as strategic steps in eradicating thuggery in Serang Regency.